Determination of Drought and Wet Periods of the Black Sea Region Using SPI Method - Yasemin Deniz Öztürk; Ramazan Ünlü (Doğal Afetler ve Çevre Dergisi)
The Black Sea region is the region with the highest rainfall in Türkiye. However, precipitation in the Black Sea region varies considerably both between years and within the region. This situation causes droughts in the region, with dry and wet periods following each other. This study aimed to determine the drought and wet periods in the Black Sea region according to the annual and 12-month SPI values. Standardized Precipitation Index (SPI) values were calculated according to the average precipitation data of 26 meteorology stations selected from the region between 1960 and 2020. The trends of the identified drought and wet periods were determined using Mann-Kendall trend analysis. In addition, using the heat map, the drought and wet periods of the Black Sea Region were determined by dividing coastal and inland areas. The analysis results determined that 1966, 1969, 1974-1977, 1984-1986, 1993-1994, 2006-2007, and 2019-2020 received less rainfall than normal and many stations had severe drought. It shows that 1967, 1988, 1996-1997, 1999, 2009, and 2016 received more precipitation than normal, that is, it has a humid character. According to the Mann-Kendall trend analysis results, it was not found that there was a decreasing trend in the coastal areas of the Western Black Sea Region. However, there was no significance in the decrease. Although there is an increasing trend in the Central and Eastern Black Sea region, this trend was found to be significant in some stations. Due to the landforms of the region, it was determined that there was not a general dry period or a general wet period and that the drought and wet periods differed in the east-west direction and the coastal-inland areas.